2017
DOI: 10.17796/1053-4628-41.6.11
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Web-Based Nationwide Korean Pediatric Dental Sedation Registry

Abstract: This is the first attempt to collect sedation data on a nationwide scale in the field of pediatric dentistry. The sedation database established with the registry may facilitate standardizing and improving pediatric dental sedation clinical practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…7,8 Registries are essential tools for providing information about the prevalence and natural history of a particular type of disease, discovering associated environmental and genetic factors, and prognosis related to different therapeutic approaches. [8][9][10][11] From administrative perspectives, patient and disease registries are efficient tools in improving health outcomes as well as reducing treatment costs. In addition, they may become useful in providing clinical guidelines and recruiting patients for clinical trial studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8 Registries are essential tools for providing information about the prevalence and natural history of a particular type of disease, discovering associated environmental and genetic factors, and prognosis related to different therapeutic approaches. [8][9][10][11] From administrative perspectives, patient and disease registries are efficient tools in improving health outcomes as well as reducing treatment costs. In addition, they may become useful in providing clinical guidelines and recruiting patients for clinical trial studies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they may become useful in providing clinical guidelines and recruiting patients for clinical trial studies. [8][9][10][11][12][13] The number, size and scope of patient registries in the field of ophthalmology have been gradually growing all around the world during the last decade. 14 A comprehensive review by Tan et al showed that a total of 85 clinical registries have been established in various fields of ophthalmology, including blindness or low vision (n = 19), corneal transplantation (n = 10), glaucoma (n = 10), cataract or refractive surgery (n = 8), retinoblastoma (n = 7), endophthalmitis or uveitis (n = 6), ocular trauma (n = 6), age-related macular degeneration (n = 5), microphthalmia or congenital ocular anomalies (n = 4), diabetic retinopathy (n = 2) and retinal detachment or macular hole (n = 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dental sedation teacher groups (DSTG) system and visual analog scale (VAS, pain during work) were used to measure the patients' anxiety during SRP. (17,18) The patients' satisfaction with the treatment was assessed using a questionnaire about their pain and discomfort levels, and the responses were recorded in categories of good, moderate, and low.…”
Section: •Smoking or Use Of Special Medications (Tranquilizers)mentioning
confidence: 99%